Studies on Lopping Intensities of Prosopis spicigera - Bhimaya, C. P.; Kaul, R. N.; Ganguli, B. N. (Indian Forester, 1964)
The lopping of trees of various fodder apecies in different statei of India has been briefly reviewed. The details regarding the intensity of lopping practices have been discussed. Field experiments conducted on fully grown Prosopis spicigera trees at Beriganga and central research farm, Jodhpur during the years 1955-58 and 1960-61 respectively have shown that intensity of lopping does not adversely affect the growth of Prosopis spicigera trees. Recurrent lopping ot trees definitety reduces the leaf fodder yield, irrespective of intensity of lopping, perhaps due to successive reduction in the overall surface of new shoots, thereby suggesting a definite need for an intervening rest period for sustained forage yield. There is, therefore, a need for evolving a system of rotational lopping giving the trees just the right period of rest which may be necessary for a sustained leaf fodder yield.